1984
DOI: 10.1128/aac.26.6.833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbaric oxyhelium gas on response of bacteria to antimicrobial agents in vitro

Abstract: Modern diving techniques can require the treatment of infection in an atmosphere of pressurized oxyhelium gas. The antibiotic susceptibility of 16 species and strains (eight genera) of gram-negative bacilli and 3 species and strains (two genera) of gram-positive cocci to each of 21 antimicrobial agents was assessed in air at atmospheric pressure and in oxyhelium gas at an absolute pressure of 7 bar (ca. 709 kPa). A disk diffusion technique was employed, and significantly different results were obtained in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
1
Order By: Relevance
“… 53 demonstrated that oxygen triggers the differentiation of fibroblasts to myofibroblasts – a possible explanation for the accelerated healing. It has also been shown in vitro that HBOT may increase the susceptibility of certain bacteria to antimicrobial agents 120 . For example, Kenward et al.…”
Section: Therapeutic Wound Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 demonstrated that oxygen triggers the differentiation of fibroblasts to myofibroblasts – a possible explanation for the accelerated healing. It has also been shown in vitro that HBOT may increase the susceptibility of certain bacteria to antimicrobial agents 120 . For example, Kenward et al.…”
Section: Therapeutic Wound Oxygenationmentioning
confidence: 99%
“…It has also been shown in vitro that HBOT may increase the susceptibility of certain bacteria to antimicrobial agents. 120 For example, Kenward et al 120 reported that under HBOT the zones of inhibition were reduced in Gram-negative bacterial cultures, whereas for Gram-positive bacteria a mixture of effects was found. It seems that these effects are quite strain specific and may not easily be generalized to all aerobic or anaerobic bacteria.…”
Section: Therapeutic Wound Oxygenationmentioning
confidence: 99%
“…De esta manera aumenta la eficiencia del proceso de limpieza de restos celulares y la defensa contra microorganismos que pudieran enlentecer la cicatrización 33,34 . Este factor tiene especial relevancia en individuos en que su sistema inmune está comprometido, como por ejemplo: pacientes diabéticos, en tratamiento inmunosupresor y con inmunodeficiencias congénitas o adquiridas 35 .…”
Section: Impacto Del Tratamiento Con Oxígeno Hiperbáricounclassified
“…The researchers found that using four sessions of HBOT, positive bacterial cultures from the lesions significantly decreased (from 19 to 3 in the study group against 16-12 in the conventional treatment group). In addition, Kenward et al 43 demonstrated the significant effect of HBOT on in vitro Gram-negative bacteria cultures.…”
Section: Oxygen-associated Therapies and Wound Healingmentioning
confidence: 99%
“…In addition, Kenward et al. 43 demonstrated the significant effect of HBOT on in vitro Gram‐negative bacteria cultures.…”
mentioning
confidence: 99%